Monitoring Real-time Temperature Dynamics of a Short RNA Hairpin Using Förster Resonance Energy Transfer and Circular Dichroism - Balcerowicz, Martin; Di Antonio, Marco; Chung, Betty (Bio-protocol, 2021)
RNA secondary structures are highly dynamic and subject to prompt changes in response to the environment. Temperature in particular has a strong impact on RNA structural conformation, and temperature-sensitive RNA hairpin structures have been exploited by multiple organisms to modify the rate of translation in response to temperature changes. Observing RNA structural changes in real-time over a range of temperatures is therefore highly desirable. A variety of approaches exists that probe RNA secondary structures, but many of these either require large amount and/or extensive processing of the RNA or cannot be applied under physiological conditions, rendering the observation of structural dynamics over a range of temperatures difficult. Here, we describe the use of a dually fluorescently labelled RNA oligonucleotide (containing the predicted hairpin structure) that can be used to monitor subtle RNA-structural dynamics by Förster Resonance Energy Transfer (FRET) at different temperatures with RNA concentration as low as 200 nM. FRET efficiency varies as a function of the fluorophores' distance; high efficiency can thus be correlated to a stable hairpin structure, whilst a reduction in FRET efficiency reflects a partial opening of the hairpin or a destabilisation of this structure. The same RNA sequence can also be used for Circular Dichroism spectroscopy to observe global changes of RNA secondary structure at a given temperature. The combination of these approaches allowed us to monitor RNA structural dynamics over a range of temperatures in real-time and correlate structural changes to plant biology phenotypes. .